the PENGARUH KOMPETENSI, KEPRIBADIAN, DAN DUKUNGAN ATASAN TERHADAP KINERJA PEGAWAI (Studi Pada PT. Perkebunan Nusantara IX Semarang) - Anisa Ayu Hartaningtyas, 14.05.51.0007; Rijanti, Tristiana (Students' Journal of Economic and Management, 2018)
This study aims to examine and analyze the influence of competence, personality, support supervisor on the performance of employees of PT. Perkebunan Nusantara IX Semarang. Respondents of this research consisted of 98 people PT. Perkebunan Nusantara IX Semarang. Data analysis used is the test of validity, reliability test and multiple linear regression analysis using IBM SPSS software version 20.0 to test and prove the research hypothesis. The result of multiple linear regression test shows that Competence has positive and significant influence to employee performance, Personality has positive and significant influence to employee performance, Supervisor Support has positive and significant influence to employee performance. Keywords: Competence, personality, Supervisor Support and Employee Performance.